Preferensi Imago Oryctes rhinoceros Dalam Memilih Limbah Tanaman Kelapa Sawit - Alwan Nurfauzan Saragih; Henry Budi Hasibuan (Jurnal Ragam Pengabdian, 2026)
This study was conducted to determine the preferences of the rhinoceros rhinoceros beetle imago in choosing a residence rather than oil palm waste. This study was conducted in the greenhouse laboratory of the Indonesian Palm Oil Technology Institute, Medan City, North Sumatra Province and took place in May 2026 for 3 weeks. In this study, data collection was carried out through several parameters, namely, the total number of imago that chose the media, the effect of temperature on the total number of beetles, the effect of humidity on the total number of imago, the ratio of males and females that chose oil palm waste. The results of this study show the preferences of Oryctes rhinoceros imago in choosing oil palm waste.